Profile and outcomes of hospitalized patients with COVID-19 at a tertiary institution hospital in Ghana - Ayisi-Boateng Nana Kwame; Owusu, Michael; Tawiah, Phyllis; Ampah, Brenda A.; Sylverken, Augustina Angelina; Wusu-Ansah, Owusu K.; Sarfo, Fred S.; Phillips, Richard Odame (Ghana Med J., 2024)
This is an article published in Ghana Med J 2020; 54(4) supplement: 39-45; doi: http://dx.doi.org/10.4314/gmj.v54i4s.7